Transgenic mice susceptible to poliovirus. - Koike, S (1991)
Poliovirus-sensitive transgenic mice were produced by introducing the human gene encoding cellular receptors for poliovirus into the mouse genome. Expression of the receptor mRNAs in tissues of the transgenic mice was analyzed by using RNA blot hybridization and the polymerase chain reaction. The human gene is expressed in many tissues of the transgenic mice just as in tissues of humans. The transgenic mice are susceptible to all three poliovirus serotypes, and the mice inoculated with poliovirus show clinical symptoms similar to those observed in humans and monkeys. Rabbit antipoliovirus serum detects the antigens mainly in motor neurons in the anterior horn of the spinal cord and in nerve cells in the medulla oblongata and pons of the paralyzed transgenic mice. Therefore, cell types sensitive to poliovirus in the central nervous system of the transgenic mice appear to be identical to those of humans and monkeys. Furthermore, many more doses of oral poliovirus vaccine strains than of the virulent strains are required to cause paralysis in the transgenic mice. This may reflect the observation that the virulent strain multiplies more efficiently in the central nervous system than the attenuated strain. Thus, the transgenic mice may become an excellent new animal model to study molecular mechanisms of pathogenesis of poliovirus and to assess oral poliovirus vaccines.